2010
DOI: 10.1142/s0217984910024638
|View full text |Cite
|
Sign up to set email alerts
|

PROPERTIES OF THE SUPERCONDUCTING GAP RATIO IN THE VAN HOVE SCENARIO OF HIGH-Tc OXIDES

Abstract: The superconducting gap ratio R = 2∆(0)/k B Tc has been studied in the context when the Fermi level is close to the van Hove singularity. In this approach, we consider the interaction is related to the phonons at low temperature but at high temperature, it is relevant to the magnetic excitations. Our results show that the superconducting gap ratio R takes large values in qualitative agreement with experimental data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…(iii) For V p = 0, we find the expression of T c obtained in a previous work. 29 In this case, T c is independent on the Debye energy and the isotope coefficient α = 0. (iv) For V p = 0, n 1 = 0 and D = J, we rediscover the Kurihara Formula.…”
Section: Calculation Of T Cmentioning
confidence: 98%
“…(iii) For V p = 0, we find the expression of T c obtained in a previous work. 29 In this case, T c is independent on the Debye energy and the isotope coefficient α = 0. (iv) For V p = 0, n 1 = 0 and D = J, we rediscover the Kurihara Formula.…”
Section: Calculation Of T Cmentioning
confidence: 98%
“…When the parameter increases from 0 to 0.6, the singularity is shifted to lower energy (Figure 3). With this form of the density of states ( = 0), we have established analytical expressions of the superconducting gap ratio R [53], the critical temperature T c and the isotope coefficient [54,55]. For a half-filling system, the Fermi level is just on the singularity F = VHS .…”
mentioning
confidence: 99%
“…22 It has been shown that high-temperature superconductivity in cuprates can be understood in terms of an interacting holespin model with super-exchange J and Kondo-type exchange interactions K. 23 In this model holes are coupled with localized Cu 2þ spins via a Kondo-type exchange interaction. In a previous work, 24 we have developed this model in the weak coupling limit and have obtained an analytical expression for the superconducting gap ratio R ¼ 2D(0)/k B T c with a van Hove singularity in the density of states. We have shown that this ratio R takes large values in qualitative agreement with experimental results.…”
mentioning
confidence: 99%